Analysis of Social Return on Investment for The Sekar Arum Domestic Wastewater Management System in Malang - Hermansyah, Dani (Green Publisher Indonesia, 2023)
The study focuses on the analysis of the Social Return on Investment (SROI) of the Sekar Arum Centralized Wastewater Treatment System (SPALD) in Malang, Indonesia. The research attempts to answer the main question regarding the economic, social, and environmental impacts produced by this program. The research methodology involved collecting both quantitative and qualitative data and consulting with stakeholders to understand their perceptions of the value and benefits of this initiative. The main findings suggest that investments in sanitation produce broad and multiplying benefits, including improved public health, reduced environmental pollution, and enhanced quality of life. The thesis delves into the significant implications of investing in sanitation and offers recommendations for increasing the effectiveness of the SPALD program. In conclusion, this thesis strengthens the understanding that investment in sanitation is a profitable and sustainable strategy that can help improve societal well-being and environmental health.